Survival analysis of Hispanics in a cohort of patients with hepatocellular carcinoma. Issue 23 (31st July 2014) - Aparo, Santiago; Goel, Sanjay; Lin, Daniel; Ohri, Nitin; Schwartz, Jonathan M.; Lo, Yungtai; Kaubisch, Andreas
Abstract : Background: Hepatocellular carcinoma (HCC) appears to have worse prognosis among Hispanics and other ethnic minorities in the United States. We investigated the overall survival (OS) of Hispanics with HCC and compared it with non‐Hispanic (NH) whites and NH blacks. Methods: Patients diagnosed and treated for HCC at an urban medical center between 2000 and 2011 were identified from the institutional cancer registry. A Cox proportional‐hazard model was used to assess survival differences between Hispanics, NH whites, and NH blacks after adjusting for clinically and statistically significant variables. Results: A total of 681 patients were identified, 24 of whom were excluded due to inability to confirm the diagnosis of HCC based on radiologic criteria and 24 due to unavailable ethnicity data. The remaining 633 patients were used for analysis. Of this final cohort, 49% (n = 309) were Hispanic, 23% (n = 144) were NH white, and 28% (n = 180) were NH black. The median OS among Hispanics was 16.3 months and was similar to that of NH whites (14.0 months) and NH blacks (17.3 months) ( P  = 0.76). Multivariate analysis revealed a hazard ratio for death for Hispanics of 0.78 (95% confidence interval 0.58‐1.07, P  = .12) when compared with NH whites and a hazard ratio for death of 0.89 (95% confidence interval 0.68‐1.19, P  = 0.46) when compared with NH blacks. Conclusions: In contrast to previous reports, Hispanics with HCC from this cohort experienced similar OS when compared with NH whites and NH blacks. Cancer 2014;120:3683–3690. © 2014 American Cancer Society . Abstract : Hispanics with hepatocellular carcinoma experience a similar outcome of overall survival when compared with non‐Hispanic whites and non‐Hispanic blacks.